Efects of dietary vitamins C and E on growth performance, hematological and biochemical parameters, skeletal abnormalities, and disease resistance against V. harveyi of hybrid groupers (Epinephelus fuscoguttatus♀×Epinephelus lanceolatus♂) - Isabella Ebi; Rossita Shapawi; Lim, Leong Seng; Annita Seok Kian Yong; Nurzafrah Mazlan; Muhammad Dawood Shah; Najamuddin Abdul Basri; Abdul Aziz Jaziri (Springer Nature, 2025)
Ensuring a well-balanced diet is paramount for the growth and productivity of farmed fsh. The interplay of nutrients, particularly essential vitamins like C and E, is crucial for supporting growth and maintaining health. This study seeks to explore the impact of varying levels of dietary vitamins C and E on the growth performance, survival rates, hematological and biochemical parameters, skeletal abnormalities, and disease resistance of hybrid grouper juveniles against Vibrio harveyi. Six experimental diets were formulated, varying in vitamin C (0, 20, and 250 mg/kg) and vitamin E (0, 50, and 800 mg/kg) contents. After a 14-week feeding trial, results revealed that vitamin C–defcient diets signifcantly reduced growth performance compared to other treatments. Interestingly, a high level of vitamin C without vitamin E supplementation produced growth efects similar to the control diet. Vitamin C and vitamin E supplementations infuenced both hepatic vitamin C and vitamin E concentrations. Surplus supplementation of vitamin C improves immune response and disease resistance of a hybrid grouper. Skeletal abnormalities were infuenced by dietary vitamin C levels. Overall, supplementation with both vitamins C and E improved growth and disease resistance in hybrid grouper juveniles. Optimal results were achieved with two specifc combinations: 18.3 mg/kg of vitamin C paired with 814.8 mg/kg of vitamin E or 271.8 mg/kg of vitamin C paired with 13.4 mg/kg of vitamin E.